1996
DOI: 10.1128/jcm.34.12.3203-3205.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytotoxic, hemolytic Aeromonas caviae clinical isolates and their identification by determining presence of a unique hemolysin gene

Abstract: Aeromonas caviae has recently been recognized as an important enteropathogen, and its hemolysin is purported to be one of the virulence factors. In this study, a total of 80 clinical isolates of Aeromonas spp. were investigated by PCR with synthetic oligonucleotides targeting a cloned hemolysin-encoding sequence from an A. caviae isolate of clinical origin. Of the 35 clinical A. caviae isolates tested, only 6 contained the target sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Many studies have suggested that as compared to A. hydrophila or A. sobria , A. caviae strains isolated from various sources are rarely able to produce virulence factors [1, 2, 4, 20, 22]. In contrast, other reports have noted that most isolates of A. caviae were able to produce several potential virulence factors [29–33]. However, as suggested by Namdari and Bottone [34, 35], the heterogeneity in the findings mentioned above, may be explained to some extent by several parameters including the incubation time of cultures, culture medium used and more importantly, the repressed toxin production due to the presence of glucose in the growth medium.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies have suggested that as compared to A. hydrophila or A. sobria , A. caviae strains isolated from various sources are rarely able to produce virulence factors [1, 2, 4, 20, 22]. In contrast, other reports have noted that most isolates of A. caviae were able to produce several potential virulence factors [29–33]. However, as suggested by Namdari and Bottone [34, 35], the heterogeneity in the findings mentioned above, may be explained to some extent by several parameters including the incubation time of cultures, culture medium used and more importantly, the repressed toxin production due to the presence of glucose in the growth medium.…”
Section: Discussionmentioning
confidence: 95%
“…According to these results, a high number of strains which possessed a battery of putative extracellular virulence traits, were prevalent mainly in highly polluted sources (stabilisation pond effluents and raw sewage) while only a few of the A. caviae isolated from low‐ or non‐polluted aquatic environments produced virulence factors. Earlier studies have suggested that A. caviae was the most frequently isolated species in human faecal samples [7–9, 31, 32]. The clinical isolates are furthermore more often described as more virulent than environmental isolates [33–36].…”
Section: Discussionmentioning
confidence: 99%
“…AERO, ACH, and ASH3 in Fig. 4C are hemolysins produced by A. hydrophila (16), A. caviae (30), and A. salmonicida (12), respectively. The sequences of these hemolysins are homologous with our hemolysin.…”
Section: Cloning and Nucleotide Sequence Analysis Of The Hemolysin Genementioning
confidence: 99%
“…(C) The amino acid sequence deduced from the above sequence is shown on line 357. The sequences of ASAl, ASAER, AERO, ACH and ASH3 are from(13),(17),(16),(30) and(12), respectively.…”
mentioning
confidence: 99%
“…Moreover, a number of PCR assays have been developed for the direct detection of A. caviae. Wang et al (1996) developed a PCR assay targeting the hemolysin gene, and their results revealed that the primers were specific to hemolytic A. caviae. Identification of A. caviae via the 16S rRNA gene has been reported, but those primers could not discriminate between closely related species such as A. jandaei (Nayduch et al 2001) and A. trota (Khan and Cerniglia 1997); therefore, an additional step is needed for identification at the species level, such as sequencing and restriction enzyme digestion.…”
mentioning
confidence: 99%